Off Earth Identification of Bacterial Populations Using 16S rDNA Nanopore Sequencing - Aaron S. Burton (Genes, 2020)
The MinION sequencer has made in situ sequencing feasible in remote locations. Following our initial demonstration of its high performance off planet with Earth-prepared samples, we developed and tested an end-to-end, sample-to-sequencer process that could be conducted entirely aboard the International Space Station (ISS). Initial experiments demonstrated the process with a microbial mock community standard. The DNA was successfully amplified, primers were degraded, and libraries prepared and sequenced. The median percent identities for both datasets were 84%, as assessed from alignment of the mock community. The ability to correctly identify the organisms in the mock community standard was comparable for the sequencing data obtained in flight and on the ground. To validate the process on microbes collected from and cultured aboard the ISS, bacterial cells were selected from a NASA Environmental Health Systems Surface Sample Kit contact slide. The locations of bacterial colonies chosen for identification were labeled, and a small number of cells were directly added as input into the sequencing workflow. Prepared DNA was sequenced, and the data were downlinked to Earth. Return of the contact slide to the ground allowed for standard laboratory processing for bacterial identification. The identifications obtained aboard the ISS, Staphylococcus hominis and Staphylococcus capitis, matched those determined on the ground down to the species level. This marks the first ever identification of microbes entirely off Earth, and this validated process could be used for in-flight microbial identification, diagnosis of infectious disease in a crewmember, and as a research platform for investigators around the world.